Expertise is crucial to prolong survival in average risk medulloblastoma: long-term results of a retrospective study. Issue 4 (August 2022) - Franceschi, Enrico; Minichillo, Santino; Tosoni, Alicia; Mascarin, Maurizio; Mura, Antonella; Di Battista, Monica; Di Nunno, Vincenzo; Gatto, Lidia; Lodi, Raffaele; Bartolini, Stefania; Brandes, Alba Ariela
Purpose: Medulloblastoma is a rare tumor in adults and the use of adjuvant chemotherapy in average risk patients is debated. Methods: Patients included in our study were ⩾16 years of age, had histologically confirmed medulloblastoma, and underwent adjuvant radiotherapy with or without chemotherapy. Average risk was defined according to the Chang classification. Results: We included 48 average-risk patients. Median follow-up was 151.5 months (95% confidence interval, 124.5–178.5). Both progression-free survival (PFS) and overall survival (OS) were significantly influenced by adjuvant chemotherapy (PFS: hazard ratio [HR], 0.334, p = 0.05; OS: HR, 0.187, p = 0.017) and by receiving the treatment in a referral center (PFS: HR, 0.250, p = 0.008; OS: HR, 0.295, p = 0.038). Conclusions: Treating patients with average-risk medulloblastoma in a referral center improves both PFS and OS, does adding adjuvant chemotherapy.